The prodigy - Lowery, David; Hanna, Robert D.; Woodyard, Rhiann; Michele, Joy.; Hollis, Jeffrey Lee.; Hanna, Ray.; Pumpuang, Patrick; Smorynski, Ron.; Prevalent Entertainment, Inc.; Phase 4 Films (Firm) (Fort Mill, SC : Distributed by Phase 4 Films, 2009)
Shy and humble, but skilled beyond her years, KG is a Kung Fu prodigy. She doubts her own talents. But when the handsome Prince Po is kidnapped by a vindictive and jealous sorceress, KG is the only one strong enough to save him. With the help of the zany but brave Master Panda, KG sets off on an adventurous rescue quest.
DVD, region 1, widescreen (enhanced); Dolby Digital stereo., NTSC.
English dialogue, Spanish subtitles.
Title from container.
Voice: Rhiann Woodyard, Joy Michele, Jeffrey Lee Hollis, Ray Hanna, Patrick Pumpuang.
Head of animation, Ron Smorynski ; editor, Mimi Snow ; character designers, David Colman, Steven Gordon.
Originally released as a motion picture in 2008.
Keywords: Gifted persons -- Juvenile films; Kung fu -- Juvenile films; Kidnapping -- Juvenile films; Pandas -- Juvenile films; Gifted persons -- Drama; Kung fu -- Drama; Kidnapping -- Drama; Pandas -- Drama; Kung fu -- Teatro; Secuestro -- Teatro; Fantasy films; Action and adventure films; Children's films; Animated films; Feature films